The relationship between Emotional Intelligence (EI) and English Language performance - Hamdzah, Nor Lailatul Azilah (Penerbit UTeM Press, 2025)
Emotional intelligence is defined as the capacity to reason about emotions. Every individual needs to have equilibrium between academic intelligence and emotional intelligence so that s/he will be able to face and take challenges in life in a healthy way. In Malaysia, (MUET) which is an entry test to university, was introduced to test the language proficiency in tertiary level. The relationship between emotional intelligence and English Language performance is becoming vital due to the claims of some researchers. Therefore, the major aims of this book are to highlight the relationship between emotional intelligence and the students' MUET performance among the undergraduate students in UTeM. This book also provides the information on the correlation between emotional intelligence and MUET achievement among undergraduate students from UTeM. Such findings have very crucial pedagogical implications in adapting and enhancing these students' level of emotional intelligence skills to enhance their English Language performance.